A Method for the Assessment of Object-Based Data by Means of a Reference Model - Herberg, Jan (The International Hydrographic Review, 2015)
This contribution provides an overview of a method developed at the Institute of Ship Operation, Maritime Transport and Simulation (ISSUS) for checking the consistency of object-based data by means of a reference model. The method was designed in the course of the research project "BANET - Baltic and North Sea ECDIS Testbed" and was used to check object-based hydrographic data. In the following, the principles and application of the method are described.